Management Information System: Tools for Achieving Administrative Effectiveness in Private Universities - Moses Adeleke Adeoye (Indonesian Journal of Multidiciplinary Research, 2023)
The major goal of this study was to demonstrate the role of management information systems (MIS) at private universities, as well as the challenges they face. The study discovered four major MIS issues: poor communication networks, insufficient finance for MIS units, insufficient MIS facilities, and insufficient computer literacy among important university executives. To implement the university's management information system more effectively and successfully, as well as to improve the organization's and employees' performance. It was recommended that the government contribute a significant amount of money to MIS units in universities yearly, that more network services be made available in all universities, and that all institutions be connected to the internet.